The Memories of NK Cells: Innate-Adaptive Immune Intrinsic Crosstalk. (19th December 2016) - Gabrielli, Sara; Ortolani, Claudio; del Zotto, Genny; Luchetti, Francesca; Canonico, Barbara; Buccella, Flavia; Artico, Marco; Papa, Stefano; Zamai, Loris
Abstract : Although NK cells are considered part of the innate immune system, a series of evidences has demonstrated that they possess characteristics typical of the adaptive immune system. These NK adaptive features, in particular their memory-like functions, are discussed from an ontogenetic and evolutionary point of view.